Studies on Copper(II) Complexes with Arylazo-Bis-Acetoximes - SINGH SHEKHAWAT, RAJENDRA (Asian Journal of Chemistry, 2010)
Copper(ll) complexes with seven arylazo-bis-acetoximes have been synthesized, characterized by standard physico-chemical methods and their infra-red spectra have been taken. The studies revealed that arylazo-bis-acetoximes formed tetra coordinated complexes with copper(II). A square-planar geometry has been proposed for these copper(ll) complexes.